2012
DOI: 10.21608/jpp.2012.84267
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF PRE-PLANTING TREATMENTS OF GARLIC (Allium sativum L.) CLOVES ON GROWTH AND YIELD UNDER MIDDLE EGYPT CONDITIONS.

Abstract: Two garlic cultivars (Eggaseed 1 and Sids 40) were selected for this study. Pre-sowing treatments of cloves were: cooling at 5 O C for 10 or 20 days, GA3 soaking at 5 ppm for 12 or 24 hrs., water soaking for 12 or 24 hrs. or without treatment (control plants). The obtained results indicated that: 1-Sids 40 cultivar was superior than cv. Eggaseed 1 in regard to plant height, leaf number / plant, fresh weight of vegetative parts and bulb dry matter percentage. On the other hand , there were insignificant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
3
2
0
1
Order By: Relevance
“…However, the lowest values of germination percentage, plant length, number of leaves/ plants, nick and bulb diameter, as well as dry weight of leaves, bulb and plant was noticed by the control. Similar results were reported by Rahman et al (2006), Ahmed and Hemada (2012) respect, the highest yield was resulted from D2 followed by D3 in the two seasons. While the lowest values of yield obtained from D1 in both seasons.…”
Section: -Vegetative Growth Measurementssupporting
confidence: 90%
See 2 more Smart Citations
“…However, the lowest values of germination percentage, plant length, number of leaves/ plants, nick and bulb diameter, as well as dry weight of leaves, bulb and plant was noticed by the control. Similar results were reported by Rahman et al (2006), Ahmed and Hemada (2012) respect, the highest yield was resulted from D2 followed by D3 in the two seasons. While the lowest values of yield obtained from D1 in both seasons.…”
Section: -Vegetative Growth Measurementssupporting
confidence: 90%
“…The increases occurred on yield and its components might be attributed to the increase in vegetative growth parameters. These results agree with Ahmed and Hemada (2012) T1: the control, T2: soaking garlic cloves (SGC) in water for 24 hours, T3: SGC in 5 ppm GA3 for 24 h, T4: SGC in water for 24 h and then placing in moist peat-moss for one day, T5: SGC in water for 24 h and then placing in moist peat-moss for two days and T6: SGC in water for 24 h and then placing in moist peat-moss until root initiation.…”
Section: -Vegetative Growth Measurementssupporting
confidence: 90%
See 1 more Smart Citation
“…However, the lowest values of germination percentage after 30 days from planting was noticed by the control (T 7 ) whereas, T 5 exhibited the lowest values for all other traits. Similar results were reported by Rahman et al (2006), Ahmed and Hemada (2012) and El-Shabasi et al (2018) who reported that Sids-40 garlic clove seed soaking in water then placing in moist peatmoss until root initiation could be recommended to produce higher yield with better quality.…”
Section: Fig 2 Changes Values In All Studied Traits As Affected By Pre -Sowing Treatments On Garlic Plants (Average Of Both Seasons)supporting
confidence: 85%
“…Rahman et al (2006) noted that application of GA 3 has the capability to break dormancy and accelerates garlic sprouting. Furthermore, Ahmed and Hemada (2012) indicated that soaking garlic cloves in water or 5 ppm GA 3 for 24 hours improved vegetative growth, bulb fresh weight, total fresh yield and cured yield. Fekry (2017) stated that soaking garlic cloves in 250 ppm GA 3 for 12 hours as pre sowing treatment increased the morphological traits, yield and its component.…”
Section: Introductionmentioning
confidence: 99%